Trends in Federal Support of Research and Graduate Education - National Research Council (The National Academies Press, 2001)
The Board on Science, Technology and Economic Policy updated its 1999 analysis (Appendix A, Securing America's Industrial Strength, 1999) of changes since 1990 in the distribution of federal research funding by field of science and engineering) by incorporating FY 1998 and FY 1999 obligations from the NSF Federal Funds survey, with particular attention to the trends in basic research support, changes in research fields' relative dependence on research-sponsoring agencies, and the relationship between changes in research support and changes in enrollment in graduate training in selected fields of research. The Board did not recommend funding levels for any discipline but addressed procedural aspects of R&D budgeting.

Readiness Issues Related to Research in the Biological and Physical Sciences on the International Space Station (The National Academies Press, 2001)

Research Opportunities for Deactivating and Decommissioning Department of Energy Facilities - National Research Council (The National Academies Press, 2001)
When the Cold War abruptly ended, DOE halted most nuclear materials production. In 1995, Congress chartered DOE's Environmental Management Science Program (EMSP) to bring the nation's scientific infrastructure to bear on EM's most difficult, long-term cleanup challenges. The EMSP provides grants to investigators in industry, national laboratories, and universities to undertake research that may help address these cleanup challenges. On several occasions the EMSP has asked the National Academies for advice on developing its research agenda. This report resulted from a 15-month study by an Academies committee on long-term research needs for deactivation and decommissioning (D&D) at DOE sites.

The Mission of Microgravity and Physical Sciences Research at NASA (The National Academies Press, 2001)

Materials Research to Meet 21st Century Defense Needs: Interim Report - National Research Council (The National Academies Press, 2001)

An Assessment of the National Institute of Standards and Technology Measurement and Standards Laboratories: Fiscal Year 2001 - National Research Council (The National Academies Press, 2001)
This volume represents the 42nd annual assessment by the National Research Council (NRC) of the technical quality and relevance of the programs of the Measurement and Standards Laboratories of the National Institute of Standards and Technology (NIST). This report provides judgments regarding the overall state of the NIST Measurement and Standards Laboratories (MSL),and offers findings to further increase the merit and impact of NIST MSL programs. It also offers in-depth reviews of each of the seven laboratories of the MSL, with findings aimed at their specific programmatic areas.

The Role of Environmental NGOs: Russian Challenges, American Lessons: Proceedings of a Workshop - National Research Council (The National Academies Press, 2001)
An NRC committee was established to work with a Russian counterpart group in conducting a workshop in Moscow on the effectiveness of Russian environmental NGOs in environmental decision-making and prepared proceedings of this workshop, highlighting the successes and difficulties faced by NGOs in Russia and the United States.

Memorial Tributes: Volume 9 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2001)
This is the 9th Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964. Under the charter of the National Academy of Sciences, the National Academy of Engineering was formed as a parallel organization of outstanding engineers. Members are elected on the basis of significant contributions to engineering theory and practice and to the literature of engineering or on the basis of demonstrated unusual accomplishments in the pioneering of new and developing fields of technology. The National Academies share a responsibility to advise the federal government on matters of science and technology. The expertise and credibility that the National Academy of Engineering brings to that task stem directly from the abilities, interests, and achievements of our members and foreign associates, our colleagues and friends, whose special gifts we remember in this book.

Summary of the Workshop on Structural Nanomaterials - National Research Council
This report provides a summary of the workshop put together by the National Materials Advisory Board which covered the following areas: synthesis and assembly of nanomaterial building blocks, characterization of nanomaterials, examples of structural nanomaterials currently in use, potential applications of nanomaterials, gaps in understanding of synthesis, assembly, chemical, and physical characterization and the need for interdisciplinary approach, as well as identification of the \

Biographical Memoirs: Volume 80 - National Academy of Sciences (The National Academies Press, 2001)
Biographic Memoirs: Volume 80 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.

Carbon Management: Implications for R&D in the Chemical Sciences and Technology - National Research Council (The National Academies Press, 2001)
Considerable international concerns exist about global climate change and its relationship to the growing use of fossil fuels. Carbon dioxide is released by chemical reactions that are employed to extract energy from fuels, and any regulatory policy limiting the amount of CO2 that could be released from sequestered sources or from energy-generating reactions will require substantial involvement of the chemical sciences and technology R&D community. Much of the public debate has been focused on the question of whether global climate change is occurring and, if so, whether it is anthropogenic, but these questions were outside the scope of the workshop, which instead focused on the question of how to respond to a possible national policy of carbon management. Previous discussion of the latter topic has focused on technological, economic, and ecological aspects and on earth science challenges, but the fundamental science has received little attention. This workshop was designed to gather information that could inform the Chemical Sciences Roundtable in its discussions of possible roles that the chemical sciences community might play in identifying and addressing underlying chemical questions.

Materials in the New Millennium: Responding to Society's Needs - National Research Council (The National Academies Press, 2001)
This book details the forum that was held by the National Materials Advisory Board at the National Academy of Sciences. The purpose of this forum was to bring the importance of materials to the attention of policy makers and to promote interactions between policy makers and the materials community. Four key themes were addressed: the critical role of materials in advancing technology and enhancing the nation's economy, security, and health, industrial and societal needs that will require materials development in the new millennium. Materials research areas with the greatest potential for meeting those needs, and federal and industrial research initiatives that can help the materials community meet those needs. To help focus this discussion, special sessions were convened to address the current and future roles of materials in four selected areas: information technology, health and biotechnology, national security, and energy and the environment.

Occupational Health and Workplace Monitoring at Chemical Agent Disposal Facilities - National Research Council (The National Academies Press, 2001)
In keeping with a congressional mandate (Public Law 104-484) and the Chemical Weapons Convention, the United States is currently destroying its chemical weapons stockpile. The Army must ensure that the chemical demilitarization workforce is protected from the risks of exposure to hazardous chemicals during disposal operations and during and after facility closure. Good industrial practices developed in the chemical and nuclear energy industries and other operations that involve the processing of hazardous materials include workplace monitoring of hazardous species and a systematic occupational health program for monitoring workers' activities and health. In this report, the National Research Council Committee on Review and Evaluation of the Army Chemical Stockpile Disposal Program examines the methods and systems used at JACADS and TOCDF, the two operational facilities, to monitor the concentrations of airborne and condensed-phase chemical agents, agent breakdown products, and other substances of concern. The committee also reviews the occupational health programs at these sites, including their industrial hygiene and occupational medicine components. Finally, it evaluates the nature, quality, and utility of records of workplace chemical monitoring and occupational health programs.

Approaches to Improve Engineering Design (The National Academies Press, 2001)
Approaches to Improve Engineering Design examines the theories and techniques for decision making under conditions of risk, uncertainty, and conflicting human values. This report attempts not only to analyze existing tools but also to identify opportunities to establish a more rigorous fundamental basis for decision making in engineering design.

Theoretical Foundations for Decision Making in Engineering Design (The National Academies Press, 2001)

Capitalizing on New Needs and New Opportunities: Government-Industry Partnerships in Biotechnology and Information Technologies - National Research Council (The National Academies Press, 2001)
This report addresses a topic of recognized policy concern. To capture the benefits of substantial U.S. investments in biomedical R&D, parallel investments in a wide range of seemingly unrelated disciplines are also required. This report summarizes a major conference that reviewed our nation's R&D support for biotechnology and information technologies. The volume includes newly commissioned research and makes recommendations and findings concerning the important relationship between information technologies and biotechnology. It emphasizes the fall off in R&D investments needed to sustain the growth of the U.S. economy and to capitalize on the growing investment in biomedicine. It also encourages greater support for inter-disciplinary training to support new areas such as bioinformatics and urges more emphasis on and support for multi-disciplinary research centers.

A Modified Baseline Incineration Process for Mustard Projectiles at Pueblo Chemical Depot - National Research Council (The National Academies Press, 2001)
The United States has maintained a stockpile of chemical warfare agents and munitions since World War I. The Army leadership has sought outside, unbiased advice on how best to dispose of the stockpile. In 1987, at the request of the Under Secretary of the Army, the National Research Council (NRC) established the Committee on Review and Evaluation of the Army Chemical Stockpile Disposal Program (Stockpile Committee) to provide scientific and technical advice and counsel on the CSDP. This report is concerned with the technology selection for the Pueblo site, where only munitions containing mustard agent are stored. The report assesses a modified baseline process, a slightly simplified version of the baseline incineration system that was used to dispose of mustard munitions on Johnston Island. A second NRC committee is reviewing two neutralization-based technologies for possible use at Pueblo. The evaluation in this report is intended to assist authorities making the selection. It should also help the public and other non-Army stakeholders understand the modified baseline process and make sound judgments about it.

Aging Avionics in Military Aircraft - National Research Council (The National Academies Press, 2001)
Extending the life of an airframe has proven challenging and costly. Extending the life of an avionics system, however, is one of the most critical and difficult aspects of extending total aircraft system lifetimes. Critical components go out of production or become obsolete, and many former suppliers of military-grade components have gone out of business. From 1986 to 1996, for example, the percentage of discontinued military\/aerospace electronic devices nearly doubled2014from 7.5 percent to 13.5 percent. In addition, legacy avionics systems, which were designed to meet requirements of the past, generally lack the full capability to perform new missions, meet new threats, or perform well in the new information-intensive battlefield environments. As the legacy aircraft fleet ages, avionics systems will become more and more difficult to support and maintain. Whereas the military once provided a large and profitable market for the electronics industry, the military electronics market today constitutes less than 1 percent of the commercial market. As a result, the military must increasingly rely on commercial off-the-shelf (COTS) technologies for its avionics hardware and software. Although COTS items are generally less expensive than comparable items designed especially to meet military specifications, the technology-refresh cycle for COTS is typically 18 months or less, which exacerbates the obsolescence problem for aircraft whose lifetimes are measured in decades. The short refresh cycle is driven mostly by the tremendous advances in computer systems, which comprise an increasing percentage of avionics content. In response to a request by the Assistant Secretary of the Air Force for Acquisition, the National Research Council convened the Committee on Aging Avionics in Military Aircraft, under the auspices of the Air Force Science and Technology Board, to conduct this study. This report summarizes the following: Gather information from DoD, other government agencies, and industrial sources on the status of, and issues surrounding, the aging avionics problem. This should include briefings from and discussions with senior industry executives and military acquisition and support personnel. A part of this activity should include a review of Air Force Materiel Command's study on diminishing manufacturing sources to recommend ways to mitigate avionics obsolescence. Provide recommendations for new approaches and innovative techniques to improve management of aging avionics, with the goal of helping the Air Force to enhance supportability and replacement of aging and obsolescing avionics and minimize associated life cycle costs. Comment on the division of technology responsibility between DoD and industry.

Thermionics Quo Vadis?: An Assessment of the DTRA's Advanced Thermionics Research and Development Program - National Research Council (The National Academies Press, 2001)
This report evaluates the Defense Threat Reduction Agency prior and present sponsored efforts; assess the present state of the art in thermionic energy conversion systems; assess the technical challenges to the development of viable thermionic energy conversion systems for both space and terrestrial applications; and recommend a prioritized set of objectives for a future research and development program for advanced thermionic systems for space and terrestrial applications.

Frontiers of Engineering: Reports on Leading-Edge Engineering From the 2000 NAE Symposium on Frontiers in Engineering - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2001)
In 1995 the National Academy of Engineering (NAE) initiated the Frontiers of Engineering Symposium program, which every year brings together 100 of the nation's future engineering leaders to learn about cutting-edge research and technical work in different engineering fields. On September 14-16, 2000, the National Academy of Engineering held its sixth Frontiers of Engineering Symposium at the Academies' Beckman Center in Irvine, California. Symposium speakers were asked to prepare extended summaries of their presentations, and it is those papers that are contained here. The intent of this book, and of the five that precede it in the series, is to describe the content and underpinning philosophy of this unique meeting and to highlight some of the exciting developments in engineering today.